Climate change and agricultural productivity in West Africa - Chimere Okechukwu Iheonu; Simplice Asongu; Ekene T. Emeka; Ebuka C. Orjiakor (African Governance and Development Institute (AGDI), 2022)
Agriculture remains one of the major sources of livelihood in West Africa. The sector accounts for a significant share of output and employment in the sub-region. However, extreme weather events have been signaled to affect the sector's productivity in recent times. In this study, we investigate the heterogeneous long-run relationship between climate change and agricultural productivity in West Africa from 1990 to 2020. Using the Augmented Mean Group (AMG) and the Common Correlated Effect Mean Group (CCEMG) estimators, we show that rising temperatures significantly reduce agricultural productivity in Gambia, Mali, Niger, and Togo. However, after accounting for endogeneity, we find that the negative relationship between temperature and agricultural productivity becomes insignificant for Niger while the positive relationship between rising temperature and agricultural productivity becomes significant for Ghana. Also, the results show that temperature Granger cause agricultural productivity in West Africa. We discussed some policy implications based on these findings.
Keywords: 330; Climate Change; Temperature; Agricultural Productivity; West Africa; Augmented Mean Group; Common Correlated Effect Mean Group